The Effects of UI Benefits on Unemployment and Subsequent Outcomes: Evidence from a Kinked Benefit Rule - Tomi Kyyrä; Hanna Pesola (Institute of Labor Economics (IZA), 2017)
This paper analyzes the effects of unemployment insurance (UI) benefits on unemployment exits and subsequent labor market outcomes. We exploit a piecewise linear relationship between the previous wage and UI benefits in Finland to identify the causal effects of the benefit level by using a regression kink design. According to our findings, higher benefits lengthen nonemployment spells and decrease time spent in part-time unemployment, and thus result in more full-time unemployment. Also the re-employment probability and post-unemployment wage are negatively affected. The results for the duration of the first post-unemployment job are not conclusive, but in total both employment and earnings in the two years following the beginning of the unemployment spell decrease with higher benefits.
Keywords: J64; J65; 330; unemployment duration; job match quality; regression kink design; unemployment insurance